1992
DOI: 10.1002/jhrc.1240151212
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of conditions in static headspace GC

Abstract: The precision and sensitivity of head‐space GC can be improved by careful selection of the operating conditions: partitioning in the vapor phase can be promoted by altering the sample matrix; the ratio of the volumes of the gaseous and liquid phases, the sample temperature, the equilibration time, and the effect of sample mixing should also be considered. Most of the principles covered here can be applied to either manual headspace GC or to headspace GC utilizing an automated sampler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The result indicated that the sensitivity of static headspace analysis increased with the rising of temperature of the headspace during 60 to 100 ℃, while it decreased beyond 100 ℃ because of thermal degradation. 20 In addition, careful attention should be paid to optimization of the heating time. The labile volatile components may decompose or be oxidized if the sample is heated overtime.…”
Section: Optimization Of Headspace Conditionsmentioning
confidence: 99%
“…The result indicated that the sensitivity of static headspace analysis increased with the rising of temperature of the headspace during 60 to 100 ℃, while it decreased beyond 100 ℃ because of thermal degradation. 20 In addition, careful attention should be paid to optimization of the heating time. The labile volatile components may decompose or be oxidized if the sample is heated overtime.…”
Section: Optimization Of Headspace Conditionsmentioning
confidence: 99%
“…It can be seen that the recoveries are rather low. In contrast with the well known solid-phase extraction, for which recovery is almost complete [22], such low values are common phenomena in SPME [3,6]. The third column of Table III shows the concentrations of volatile aldehydes measured by headspace SPME analysis of a sunflower oil sample of peroxide value 21 meq kg -1.…”
Section: Quantification Of Aliphatic Aldehydesmentioning
confidence: 94%
“…It is recommended that SPME quantification is performed by comparison with spiked blank matrix or by standard addition [22]. When headspace SPME is used for foods the lipid material markedly reduces the response of the detector and increases the detection limit [23].…”
Section: Quantification Of Aliphatic Aldehydesmentioning
confidence: 99%
“…The advantages of this method for analysis of essential oil compounds include saving time, solvent-free, small amounts of samples, low cost, and low detection limit [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%